CLINICAL EVALUATION OF THE HEALING PROCESS OF ORAL SOFT TISSUE SURGICAL WOUNDS STIMULATED BY LOW-LEVEL LASER THERAPY. - Hristina Lalabonova; Elena M. Ilieva (Peytchinski Publishing, 2013)
During the past decades laser therapy gained much popularity in clinical practice. Low-level lasers offer alternative solutions to numerous problems in oral surgery.Purpose: The purpose of the present study is to evaluate clinically the healing process of soft tissue surgical wounds in the oral cavity stimulated by low-level laser therapy (LLLT).Materials and methods: One hundred and twenty surgical wounds were assigned to three groups: Group I included 40 patients who underwent red spectrum LLLT with wavelength (λ) of 658 nm;Group ІІ - 40 patients treated with infra-red LLLT with λ of 904 nm;Group ІІІ (control group) - 40 patients without LLLT. In Group І and ІІ the LLLT procedures were applied 1 day before, in the day of and 1 day after the operation. Distant emission with a focused beam through an angled conical probe 3 mm in diameter (ø3mm) was used. The irradiated area is 0,5 cm2. The area of impact is the surgical wound zone and the neighboring 0,5-1,0 cm of the adjacent oral mucosa.Results and discussion: The evaluation of the healing process included the following criteria: pain, edema, hyperemia, time for wound closure, postoperative complications.Conclusions: LLLT applied with the offered treatment modality accelerates the healing process of soft tissue surgical wounds in the oral cavity, reduces treatment time and restores patients' comfort.